Do more hours in center‐based care cause more externalizing problems? A cross‐national replication study. Issue 2 (16th November 2022) - Rey‐Guerra, Catalina; Zachrisson, Henrik D.; Dearing, Eric; Berry, Daniel; Kuger, Susanne; Burchinal, Margaret R.; Nærde, Ane; van Huizen, Thomas; Côté, Sylvana M.
Abstract: Whether high quantities of center‐based care cause behavior problems is a controversial question. Studies using covariate adjustment for selection factors have detected relations between center care and behavior problems, but studies with stronger internal validity less often find such evidence. We examined whether within‐child changes in hours in center‐based care predicted changes in externalizing problems in toddlers and preschoolers ( N = 10, 105; 49% female; data collection 1993–2012) in seven studies, including from Germany, Netherlands, Norway, two from Canada and two from the U.S. Race/ethnicity data were only collected in the United States (57% and 80% White; 42% and 13% African‐American; 1.2% and 5% Latinx). Meta‐analyses showed no association ( r = .00, p = .88) between hours in center‐based care and externalizing problems.